Nicolasa Gotay Norales (1973…) A story of revisibilization of the garifuna culture (2016)
She is an African descent teacher belonging to the Garifuna ethnic group. She worked pro bono in a poor neighborhood in her hometown, where she founded the kindergarten and gave literacy classes to soldiers. With her salary, she used to buy school supplies for children. Currently, she teaches in the school where she completed her primary education and where, as a child, she was not allowed to speak her mother tongue. She promotes education according to the linguistic and cultural reality of her people. Her classroom is a sample of Garifuna cultural elements such as fishing, food, and other values. This work emerged in the frame of the research project entitled African and African Descendant Teachers in Colombia, Brazil, Guatemala, Venezuela, Equatorial Guinea in the century XX-XXI, within a research line on Latin American Educators. Life history method and qualitative approach were applied. Field visits were carried out, interviews were conducted with Nicolasa, with people who know her and some relatives. It is evident that her educational practice has been influenced by the resilience, pride and persistence of Garifuna women. Her determination to start a Kindergarten school, to recover and to inform students and community about the worldview and values of the Garifuna culture; including language, dance, and music demonstrate her high sense of responsability and commitment to teaching. Nicolasa impacts on the social, cultural and political processes in favor of a change of mind in a society that has suffered discrimination and racism for many years, in order to project a cultural identity and educational development for the benefit and continuous improvement of Garifuna people.